FAKTOR - FAKTOR YANG MEMPENGARUHI MINAT KARIR MAHASISWA KELAS KARYAWAN PROGRAM STUDI BK UNIVERSITAS PGRI SEMARANG - Imarotul Aliyah; Heri Saptadi Ismanto; Agus Setiawan (STKIP Subang, 2023)
The aim of this research is to determine the factors that influence the career interest of employee class students in the BK study program at PGRI University Semarang. Factors that influence the career interests of students in the employee class of the BK study program at PGRI University Semarang are measured by the variables of interest, academic achievement, type of work chosen, and parental expectations. The sample in this research were students from the employee class of the BK study program at PGRI University Semarang. Data analysis uses data reduction type analysis techniques, presenting data and drawing conclusions regarding the factors that influence the career interests of employee class students in the BK study program at PGRI University Semarang. The results of the research show that the factors that influence the career interests of students in the employee class of the BK study program at PGRI University Semarang include internal factors and external factors. Where internal factors consist of interest and academic achievement, while external factors consist of the type of job chosen and salary or income.